FAAH INHIBITION IS PROTECTIVE IN A CELL CULTURE MODEL OF PARKINSON'S DISEASE. (29th November 2012) - Zeissler, M; Hanemann, CO; Zajicek, JP; Carroll, CB
Abstract : Background: Levels of the endocannabinoid anandamide (AEA) are elevated in Parkinson's disease (PD) patients. We have recently demonstrated that the cannabinoid Δ9-tetrahydrocannabinol is neuroprotective via activation of the peroxisome proliferator-activated receptor gamma (PPARγ) receptor which AEA can also activate. Levels of AEA can be raised endogenously by inhibiting its hydrolysis through fatty acid amide hydrolase (FAAH). We therefore investigated whether FAAH inhibition is protective in our cell culture model of PD. Methods: SH-SY5Y neuroblastoma cells were differentiated with retinoic acid. The PD relevant neurotoxin MPP+ was co-administered with the FAAH and PPARγ inhibitors (URB597 and T0070907) for 48 h after which cell death was determined using the LDH assay and production of reactive oxygen species (ROS) measured. Protein levels of PPARγ were determined by Western blotting. Results: URB597 was protective against MPP+ toxicity which was blocked by T0070907. However, administration of URB597 alone or with MPP+ did not significantly increase PPARγ expression. Increased expression of the receptor is thought to be an indicator of its activation. Furthermore, the MPP+ induced increase in ROS production was reduced by URB597. This effect was not reversed by T0070907. Conclusions: Although our results are thus far inconclusive regarding the involvement of the PPARγ receptor, we have shown that URB597 may be neuroprotective by down-regulating ROS formation.